2018
DOI: 10.1111/jvh.12886
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hepatitis C virus leads to economic gains related to reduction in cases of hepatocellular carcinoma and decompensated cirrhosis in Japan

Abstract: Hepatocellular carcinoma (HCC) is a serious complication of hepatitis C virus (HCV) infection. Sustained virologic response (SVR) for HCV is associated with a reduction in cirrhosis, HCC and mortality and their associated costs. Japanese HCV patients are older with higher prevalence of HCC. Here we used a decision-analytic Markov model to estimate the economic benefit of HCV cure by reducing HCC and DCC burden in Japan. A cohort of 10 000 HCV genotype 1b (GT1b) Japanese patients was modelled with a hybrid deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Although we did not observe decreased costs in the DAA group among patients without cirrhosis, we believe that over time the savings associated with the avoidance of advanced liver disease and other complications of HCV will be offset, as predicted by several economic investigations in which DAA therapy was found to be cost-effective in the long term. (16)(17)(18)31) Furthermore, although we did not study HCV-associated extrahepatic manifestations in this study, previous investigators found that a large proportion of all-cause medical costs were attributable to extrahepatic manifestation-related costs in patients with HCV, adding strength to our findings that treatment with DAAs can reduce the high medical costs in patients with HCV by saving in both liver complications and extrahepatic manifestations avoided with cure. (14,32,33) It is important to note that in our economic analysis, we estimated that the costs for at least an 8-week DAA treatment course ranged between approximately $100,467 and $123,086.…”
Section: Discussionmentioning
confidence: 65%
“…Although we did not observe decreased costs in the DAA group among patients without cirrhosis, we believe that over time the savings associated with the avoidance of advanced liver disease and other complications of HCV will be offset, as predicted by several economic investigations in which DAA therapy was found to be cost-effective in the long term. (16)(17)(18)31) Furthermore, although we did not study HCV-associated extrahepatic manifestations in this study, previous investigators found that a large proportion of all-cause medical costs were attributable to extrahepatic manifestation-related costs in patients with HCV, adding strength to our findings that treatment with DAAs can reduce the high medical costs in patients with HCV by saving in both liver complications and extrahepatic manifestations avoided with cure. (14,32,33) It is important to note that in our economic analysis, we estimated that the costs for at least an 8-week DAA treatment course ranged between approximately $100,467 and $123,086.…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, DAA therapy does not increase the risk of HCC recurrence but does decrease the risk of waitlist dropout due to tumour progression or death . Using a hybrid decision tree model and a Markov state transition model to capture the natural history of HCV over a lifetime horizon of a cohort of 10 000 GT1 CHC patients, one study from Japan indicated that treatment with DAAs could eliminate HCC in 2057 cases and decompensated cirrhosis in 1478 cases, thus leading to significant direct and indirect economic gains …”
Section: Discussionmentioning
confidence: 99%
“…In non-cirrhotic patients, the disease progression is stopped when SVR12 is achieved. Patients with cirrhosis may still develop decompensated cirrhosis (DCC) or hepatocellular carcinoma (HCC) despite reaching SVR12, but the likelihood of this is significantly lower compared to patients without SVR12 [28]. The transition probabilities are derived from available literature and shown in Table 2.…”
Section: Model Structurementioning
confidence: 99%